Piscicultura orgânica: equivalência e harmonização entre as normas nacional e internacionais e a aplicabilidade do plano de manejo para certificação participativa - Remor, Eliane (2016)
The demand for aquaculture products, especially those produced with social and environmentally practices, is growing worldwide. Countries and markets are adopting labeling and certification standards as a way to differente these products from conventional. In this context, the aim of the present study, is to verify the equivalence and harmonization between national legislation and international standards for organic aquaculture production. Therefore, the Inter-Ministerial Instruction No 28, 2011 (IN 28/2011), which establishes technical standards for organic aquaculture systems production, was compared with public international standards in countries on four continents in order to verify the degree harmonization and the possibility of equivalence with the Brazilian standard. Equitool was the tool used, with adjustments for comparison and verification of the degree of harmonization and equivalence between the standards: Brazilian (IN 28/2011), the European Union (EU) (EC: 834/07, 710/09 and 1358 / 14), Canada (32 312 CAN / 2012), Australia (Australian Certified Organic Standard 2013) and China (GB / T19630 / 2011). From bibliographical, documentary studies and particularly in view of the IN 28/2011 requirements for organic aquaculture production, it was developed a management plan to be tested theoretically. The implementation of the management plan was carried in visits to agro-ecological properties and semistructured interviews was applied. As a result of the comparison, it was found that the Brazilian standard is more harmonized with the requirements of the Chinese standard. The main non-compliances are primarily with the European standard, then with the Australian and the Canadian standard respectively. Among the criteria studied, it was observed that the largest differences are found as the division of the conversion periods for the organic system, feeding and prophylactic use in animals. The certification of organic aquaculture in the countries studied is predominantly carried out by audit Certification Bodies (OC) it was identified in the research Conformity Assessment Participatory Organisations (OPAC) that have certified aquaculture products. The diagnosis for the preparation of the management plan revealed the main problems to produce organic fish in a rural family property. Even considering that the studied farm has made great ecological emprovements, agroecological converted, many structural adjustments would have to be implemented, resulting in costs and increase in family work. In addition, the lack of knowledge about organic management in fish farming would require trainning for producers, as well as the lack of nutritionally adequate and organic food to provide fish dificult reprodution. It concludes that organic fish farming in rural households is an activity with great potential for the diversification of production and aggregation of income for small farmers, but there is still a long way to go before its consolidation in Cantuquiriguaçu territory.